Sensing Lipids with Mincle: Structure and Function - Williams, Spencer J. (Frontiers in Immunology, 2017)
Mincle is a C-type lectin receptor that has emerged as an important player in innate immunity through its capacity to recognize a wide range of lipidic species derived from damaged/altered self, and foreign microorganisms. Self-ligands include sterols (e.g. cholesterol), and -glucosylceramides, and the protein SAP130, which is released upon cell death. Foreign lipids comprise those from both microbial pathogens and commensals and include glycerol, glucose and trehalose mycolates, and glycosyl diglycerides. A large effort has focused on structural variation of these ligands to illuminate the structure-activity relationships required for agonism of signalling though Mincle, and have helped identify key differences in ligand recognition between human and rodent Mincle. These studies in turn have helped identify new Mincle ligands, further broadening our understanding of the diversity of organisms and lipidic species recognized by Mincle. Finally, progress towards the development of Mincle agonists as vaccine adjuvants providing humoral and cell-mediated immunity with reduced toxicity is discussed.